Impact of 17beta-Estradiol (E2), in Increasing Immunity Against COVID-19 and Mitigating Severe COVID-19 Outcomes - Malik, Saba (Technium BioChemMed, 2021)
Men are likely to die from COVID-19 more often than women. There is a need to search out an element that gives immunity to women. Substantial amounts of estrogens (17?-ESTRADIOL) are found in men and women. To see the current situation of the COVID-19 pandemic my research aims to find the impact of 17?-estradiol (E2), in increasing immunity against COVID-19 and mitigating severe COVID-19 outcomes. A total of 113 pharmacists and doctors from different hospitals, in different provinces of Pakistan, filled questionnaires. 73.5% of doctors and pharmacists response positively on using 17?-ESTRADIOL (E2) as an element of increasing immunity against COVID-19 while 8.8 percent disagreed on that point and 17.7% of those answered go with the possibility. We got a significant result from our study. After the analysis of the whole research, we can conclude that Yes! 17?-estradiol (E2) helps in increasing immunity against COVID-19 and mitigating severe COVID-19 outcomes because estrogen acts directly on the nasal immune system by increasing phagocyte activity, dendritic cells, and natural killers. When triggered, these cells can kill the virus preventing it from spreading to the lower respiratory tract or reducing the viral (virulence) charge.